Operational Risk and Bank Profitability: Analyzing BOPO and Efficiency Ratios in Indonesian Commercial Banks - Panji Irawan; Evita Damayanti; Riza Putri Pratama; Lina Denita Siagian; Dewi Hanggraeni (Publikasi Indonesia, 2025)
The banking industry has a crucial role in the financial stability of a country. In this context, operational risk management is an important factor that affects the profitability of banks. This study aims to analyze the relationship between operational risk, which is measured using Operating Costs to Operating Income (BOPO) and Efficiency Ratio, on the profitability of commercial banks in Indonesia represented by Return on Assets (ROA). This study uses panel data from 49 commercial banks in Indonesia during the period Q3 2012 to Q3 2024. The analysis was carried out using the Ordinary Least Squares (OLS), Fixed Effects, and Random Effects methods to identify the impact of operational risks on profitability. The results show that BOPO and Efficiency Ratio have a significant negative influence on ROA. This indicates that increased operational risk, both through cost efficiency and asset efficiency, can reduce bank profitability. In addition, macroeconomic variables such as Gross Domestic Product (GDP) and bank-specific variables such as Non-Performing Loans (NPLs) were also found to have a significant effect on ROA. This study emphasizes the importance of implementing effective operational risk management strategies to improve bank financial performance. This study contributes by providing empirical evidence on the relationship between operational risk and profitability in the context of Indonesian banking, and offers recommendations for strengthening operational risk management through cost efficiency, regulatory compliance, and strengthening internal oversight.